Developing a Standardized Single Nucleotide Polymorphism Panel for Rangewide Genetic Monitoring of Bull Trout. (1st December 2021) - Bohling, Justin; Von Bargen, Jennifer; Piteo, Matthew; Louden, Amelia; Small, Maureen; Delomas, Thomas A.; Kovach, Ryan
Abstract: Conservation of threatened and endangered species often involves large‐scale collaboration across jurisdictional boundaries, but such efforts are typically hampered by a lack of consistent monitoring data at local, regional, and species‐distributional scales. Contemporary methods of genetic monitoring that are grounded in sequencing‐based approaches offer a powerful means to achieve the data consistency necessary for conservation of high‐profile species. Here, we describe the collaborative, multiagency development of a genotyping‐in‐thousands by sequencing panel for genetic monitoring of threatened Bull Trout Salvelinus confluentus across its range in North America. The resulting panel consists of 266 single nucleotide polymorphisms, a subset of which differentiate Salvelinus species (Arctic Char S. alpinus, Brook Trout S. fontinalis, Bull Trout, Dolly Varden S. malma, Lake Trout S. namaycush, and Whitespotted Char S. leucomaenis ), as well as one sex ID locus. We then used case studies from the Pacific Northwest and northern Rocky Mountains to demonstrate the efficacy of the panel for addressing local conservation needs (e.g., genetic variation, genetic differentiation, genetic assignment tests, and number of effective breeders) and compatibility with legacy data sets. Future genotyping with this panel will provide opportunities for improved conservation prioritization across the species range and collaboration among the numerous agencies charged with conserving this species. This effort provides framework to develop population genetic tools that will contribute to robust and efficient monitoring of biodiversity.